2009
DOI: 10.1080/11250000802687461
|View full text |Cite
|
Sign up to set email alerts
|

Molecular taxonomy and phylogeny of ItalianLepidurustaxa (Branchiopoda: Notostraca)

Abstract: Notostraca taxonomy is controversial, mainly owing to the high intraspecific variability of morphological characters; other complexity factors are represented by the consistent rate of reproductive variation. We undertook the molecular analyses of Italian Lepidurus taxa through the characterization of 12S, 16S and COI mitochondrial genes in new L. apus demes and in the L. couesii populations recently discovered in Southern Italy. For L. apus, the analysis of a wider data set (both in terms of molecular markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
(43 reference statements)
2
12
0
Order By: Relevance
“…It also is paraphyletic with respect to the remaining congeneric species, and despite several previous molecular studies dealing with this taxon (e.g. Mantovani et al, 2004Mantovani et al, , 2009Vanschoenwinkel et al, 2012), its level of diversification still had been underestimated, as demonstrated by the discovery of a new, highly diverged lineage within L. apus lubbocki ('L. apus lubbocki 2'), which occurs in Israel.…”
Section: Phylogenymentioning
confidence: 99%
See 4 more Smart Citations
“…It also is paraphyletic with respect to the remaining congeneric species, and despite several previous molecular studies dealing with this taxon (e.g. Mantovani et al, 2004Mantovani et al, , 2009Vanschoenwinkel et al, 2012), its level of diversification still had been underestimated, as demonstrated by the discovery of a new, highly diverged lineage within L. apus lubbocki ('L. apus lubbocki 2'), which occurs in Israel.…”
Section: Phylogenymentioning
confidence: 99%
“…(see Section 1). Regarding L. apus lubbocki, Mantovani et al (2009) already concluded that it should be recognised as a separate species, but they refrained from formally reinstating its species status (see Section S.8). Indeed, further investigations including morphology are needed to clarify its taxonomy, especially since we have demonstrated that this subspecies is not even monophyletic.…”
Section: Taxonomymentioning
confidence: 99%
See 3 more Smart Citations